FAK Family Kinases: A Potential Therapeutic Target for Atherosclerosis - Guan X; Liu Y; An Y; Wang X; Wei L; Qi X (Diabetes, Metabolic Syndrome and Obesity, 2024)
Xiuju Guan,1 Yue Liu,2 Yajuan An,1 Xinshuang Wang,1 Liping Wei,2 Xin Qi2 1School of Graduate Studies, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 2Department of Cardiology, Tianjin Union Medical Center, Tianjin, People’s Republic of ChinaCorrespondence: Xin Qi, Email qixinx2011@126.comAbstract: Atherosclerosis (AS) is a chronic progressive inflammatory disease of the vascular wall and the primary pathological basis of cardiovascular and cerebrovascular disease. Focal adhesion kinase (FAK) and proline-rich tyrosine kinase 2 (Pyk2), two highly homologous members of the FAK family kinases, play critical roles in integrin signaling. They also serve as scaffolding proteins that contribute to the assembly of cellular signaling complexes that regulate cell survival, cell cycle progression, and cell motility. Research indicates that the FAK family kinases is involved in the gene regulation of vascular cells and that aberrant expression of this family is associated with pathological changes in vascular disease. These findings establish the FAK family kinases as a critical signaling mediator in atherosclerotic lesions and inhibition of its activity has the potential to attenuate the pathological progression of AS. This review highlights the indispensable role of the FAK family kinases in abnormal vascular smooth muscle cell proliferation, endothelial cell dysfunction, inflammation, and lipid metabolism associated with AS. We also summarize therapeutic targets against the FAK family kinases, providing valuable insights into therapeutic strategies for AS.Keywords: FAK family kinases, atherosclerosis, inhibitors, cellular signaling